Early stages of catalyst aging in the iridium mediated water oxidation reaction. Issue 16 (4th April 2016) - Hetterscheid, Dennis G. H.; van der Ham, Cornelis J. M.; Diaz-Morales, Oscar; Verhoeven, M. W. G. M. (Tiny); Longo, Alessandro; Banerjee, Dipanjan; Niemantsverdriet, J. W. (Hans); Reek, Joost N. H.; Feiters, Martin C.
Abstract : The structure of an iridium Cp* water oxidation catalyst was evaluated as a function of time and applied potential. Abstract : When exposed to a potential exceeding 1.5 V versus RHE for several minutes the molecular iridium bishydroxide complex bearing a pentamethylcyclopentadienyl and a N -dimethylimidazolin-2-ylidene ligand spontaneously adsorbs onto the surface of glassy carbon and gold electrodes. Simultaneously with the adsorption of the material on the electrode, the evolution of dioxygen is detected and modifications of the catalyst structure are observed. XPS and XAS studies reveal that the species present at the electrode interface is best described as a partly oxidized molecular species rather than the formation of large aggregates of iridium oxide. These findings are in line with the unique kinetic profile of the parent complex in the water oxidation reaction.